Risk Factors of Mental Health in Adolescents: Emotional, Behavioral, Family, and Peer Relationship Problems. (29th March 2019) - Aldam, Satria Fajrullah Said; Keliat, Budi Anna; Wardani, Ice Yulia; Sulistiowati, Ni Made Dian; Florensa, Maria Veronika Ayu
ABSTRACT: Adolescents are vulnerable to some risk factors in their lives, such as emotional and behavioral problems, problems in the family, and relationship problems within their peer group. This study aimed to describe these risk factors in adolescents. This study used a descriptive statistic design with a cross-sectional approach. The study sample consisted of 292 students in the 8th grade at a junior high school, selected through a purposive sampling technique. The adolescents experienced emotional and behavioral problems, as well as relationship problems with their peers, which within the study was categorized as normal, while problems in the family have the borderline score. It is essential to promote mental health in adolescents in order to maintain good emotional conditions and behaviors, as well as good relationships within their peer group. In the meantime, mental health promotion programs should be given to adolescents and their families to prevent problems among adolescents that will affect their mental health condition.